"Cumulative Stress": The Effects of Maternal and Neonatal Oxidative Stress and Oxidative Stress-Inducible Genes on Programming of Atopy. (18th July 2016) - Manti, Sara; Marseglia, Lucia; D'Angelo, Gabriella; Cuppari, Caterina; Cusumano, Erika; Arrigo, Teresa; Gitto, Eloisa; Salpietro, Carmelo
Abstract : Although extensive epidemiological and laboratory studies have been performed to identify the environmental and immunological causes of atopy, genetic predisposition seems to be the biggest risk factor for allergic diseases. The onset of atopic diseases may be the result of heritable changes of gene expression, without any alteration in DNA sequences occurring in response to early environmental stimuli. Findings suggest that the establishment of a peculiar epigenetic pattern may also be generated by oxidative stress (OS) and perpetuated by the activation of OS-related genes. Analyzing the role of maternal and neonatal oxidative stress and oxidative stress-inducible genes, the purpose of this review was to summarize what is known about the relationship between maternal and neonatal OS-related genes and the development of atopic diseases.